Effect of Papaya Leaf Extract (Carica papaya L.) Oral on Malondialdehyde (MDA) Levels in Vitiligo Model Mice - Nurul Hidayati; Nurrachmat Mulianto; Arie Kusumawardani; Muhammad Eko Irawanto; Suci Widhiati (Journal of Social Research, 2026)
Vitiligo is a multifactorial skin disorder associated with oxidative stress and increased malondialdehyde (MDA) levels. Papaya leaf extract (Carica papaya L.) has antioxidant and anti-inflammatory properties that may inhibit its pathogenesis. This research aims to analyze the effect of papaya leaf extract on MDA levels in vitiligo model mice. This was an in vivoexperimental study using C57BL/6 mice divided into control and treatment groups, including papaya leaf extract (1500 mg) and/or 0.05% clobetasol propionate. Vitiligo was induced with 40% monobenzone for 16 days, followed by 28 days of treatment. Serum and tissue MDA levels were measured using ELISA and analyzed with the Kruskal–Wallis and Dunn tests (p < 0.05). Administration of 40% monobenzone cream significantly increased serum MDA levels in vitiligo model mice (p ? 0.001) compared to mice without vitiligo. The administration of papaya leaf extract significantly reduced serum MDA levels (p ? 0.001) in vitiligo mice compared to untreated vitiligo mice. Tissue MDA levels in vitiligo mice given combination therapy of papaya leaf extract and 0.05% clobetasol propionate cream were significantly different (p ? 0.001) compared to those receiving papaya leaf extract alone or standard topical therapy. Papaya leaf extract lowers serum MDA levels in vitiligo model mice. Tissue MDA levels in vitiligo model mice were lower with combination therapy of papaya leaf extract and 0.05% clobetasol propionate cream compared to papaya leaf extract alone or standard topical therapy.